Comparative analysis between performing a feet examination of people with diabetes and the use of the CARPeDIA application for the prevention of diabetic foot ulcer (Research, Society and Development, 2024)
Introduction: The complications of Diabetes Mellitus can be diverse and can develop quickly, with diabetic foot ulcers being the highlight in this research. Objective: To carry out a comparative analysis between the use of the CARPeDIA application and the results of examining the feet of people with diabetes. Method: descriptive study, with a quantitative approach, of comparative analysis, carrying out a comparative investigation between the use of the CARPeDIA application and the inspection of the feet of people with diabetes. The data were collected at the Centro Universitário de Lavras, on the days of the extension project Pé em dia = Pé com vida (CAAE 60224222.2.0000.5116). Results: the results were able to extract data presented by the use of the application and the results obtained during the nursing consultation. The research had a sample of 20 participants, it was possible to observe a female audience, a profile of elderly people and those with type 2 diabetes. It should be noted that the use of the app and the examination of patients' feet are complementary. The app helps the patient identify the risk of ulcers and promotes self-care, and the exam complements the analysis by identifying changes already installed. Final considerations: The comparative analysis between carrying out the exam and using the application is essential in preventing ulcers in patients with diabetic foot.